An investigation into lexical stylistic devices used in “ho chi minh: a life” by william j. Duiker - Nguyễn,Thị Thanh Thảo. (2016)
Stylistics and stylistic devices, for a long time, have been considered as the fundamental factor in creating the beauty of any literary works. However, they are not fully appreciated in the teaching and learning of English Literature. This study is carried out with the aim of giving a living proof of the natural bridge between stylistic devices and literature. Through a careful investigation into metaphor and simile by both qualitative and quantitative methods - the two typical stylistic devices which are used concentratedly and distinctively in the work “Ho Chi Minh: A Life” of William J. Duiker, and undoubtedly create the aesthetico-cognitive effect of this masterpiece, I truly hope to prove the important role of stylistics and stylistic devices to literary analysis. I found that, during the research, the contribution of metaphors and similes are variable such as helping readers comprehend the implication of the author, bringing the aesthetic-cognitive value of the work, as well as synthetizing the picture of the contemporary Vietnamese society. Finally, based on the findings and results of this study, some implications for the teaching and learning of English literature will also be suggested.